2017
DOI: 10.1021/acs.chemmater.6b04029
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Thermal Atomic Layer Deposition of Silver Thin Films

Abstract: The growth of Ag thin films by thermal atomic layer deposition (ALD) was studied. A commercial Ag compound, Ag­(fod) (PEt3), was applied with a reducing agent, dimethyl amineborane (BH3(NHMe2)). A growth rate of 0.3 Å/cycle was measured for Ag at a deposition temperature of 110 °C. The purity of the particulate, polycrystalline Ag thin films was studied with time-of-flight elastic recoil detection analysis (TOF-ERDA) and X-ray photoelectron spectroscopy (XPS). TOF-ERDA showed only small amounts of impurities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Generally, it should be noticed that the size of silver nanoparticles depends on the number of cycles and the substrate type (TNT, TNN), which is illustrated in Figure 10 . The ALD cycles number increase leads to the increase of Ag grains diameter regardless of the substrate type, which is associated with the continued nucleation and nanoparticles coalescence [ 60 , 61 ]. Morphology studies revealed the noticeable influence of the substrate type on the diameter of the deposited Ag grains.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, it should be noticed that the size of silver nanoparticles depends on the number of cycles and the substrate type (TNT, TNN), which is illustrated in Figure 10 . The ALD cycles number increase leads to the increase of Ag grains diameter regardless of the substrate type, which is associated with the continued nucleation and nanoparticles coalescence [ 60 , 61 ]. Morphology studies revealed the noticeable influence of the substrate type on the diameter of the deposited Ag grains.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] This chemistry does not extend to Ta metal and TaSix films are produced instead. 21,22 Subsequently, BH3(NHMe2) has been used to deposit Cu and other first row transition metal films [23][24][25] and has also been evaluated for Ag 26 and Au 27 metal ALD, but film growth in all cases is highly substrate dependent. Thus, there is a great need to develop new volatile reducing agents for ALD of these challenging elements and materials.…”
Section: Introductionmentioning
confidence: 99%
“…ALD can be used to deposit a wide range of materials, such as oxides, nitrides, and pure metals (copper, gold, platinum, etc.) [14]. Since the deposition is controlled by the number of active sites on the surface rather than the amount of precursor in the system, i.e., self-limiting, ALD can produce continuous films with precise thickness and exceptional conformality and uniformity on complex surfaces and structures including trenches and vias with high-aspect ratio.…”
Section: Figure 22 a Schematic Of An Ald Cyclementioning
confidence: 99%